The impact of quality foundational skills on youth employment in Africa: Does institutional quality matter? - Olagunju, Kehinde Oluseyi; Ogunniyi, Adebayo; Oguntegbe, Kunle F.; Oyetunde-Usman, Zainab A.; Adenuga, Adewale Henry; Andam, Kwaw S. (International Food Policy Research Institute, 2020)
Despite impressive progress in the economic performance of many African countries in recent years, youth unemployment remains one of the continent’s main socioeconomic and political problems. This study employs panel data covering 49 African countries for the period 2000–2017 to provide the first attempt to explicitly examine the dynamic relationship between quality foundational skills, measured by basic education quality (teacher-pupil ratio), and youth unemployment, while considering the conditional role of institutional capacity, measured by control of corruption, regulatory quality, and financial development. The empirical estimation in this paper is based on a two-step system generalized method of moments (SGMM), in order to control for unobserved heterogeneity and potential endogeneity of all the explanatory variables. The following are the main findings: First, youth unemployment is persistent in Africa. Second, quality of basic education exerts a negative impact on youth unemployment. Third, greater control of corruption, improved regulatory quality, and better structured financial sectors strengthen the effect of quality basic education in reducing youth unemployment. These findings provide a clear policy pathway for reducting youth unemployment. In particular, we recommend that better quality basic education, a well-structured financial structure, and institutional quality should constitute a fundamental component of the policy mix to reduce youth unemployment in Africa.